Multiloculated Klebsiella liver abscess successfully treated with early laparoscopic drainage after failed percutaneous drainage: a case report - Nakahara, Shun; Hirao, Yusuke; Kawahara, William; Sripusanapan, Adivitch; Lian, Kuo-Chiang (AME Case Reports; Vol 10 (May 30, 2026): AME Case Reports, 2026)
Klebsiella pneumoniae liver abscess is characterized by an aggressive clinical course with a high risk of metastatic complications. Early initiation of appropriate antibiotics and timely drainage are essential for successful management. However, large multiloculated Klebsiella pneumoniae liver abscesses are associated with a high risk of percutaneous drainage failure.